Track Record : Lessons from IFC's Corporate Governance Experience - International Finance Corporation (Washington, DC, 2017)
This book of SmartLessons is a compendium of our knowledge on implementing corporate governance projects. The lessons represent an impressive body of work, with individual contributions written by our staff—the people who really know what they are talking about, because they are out there, engaged in the work on a day-to-day basis. It reflects the evolution of our project approach as the world has changed. In the early years of our work, efforts focused on the newly independent and newly market-driven nations of the former Soviet Union. More recently, projects have addressed the sometimes rocky road to stability for emerging market countries as they struggle to regain economic momentum in the wake of the global financial crisis. Meanwhile, new opportunities and new challenges lie ahead as events in the Middle East and North Africa underscore the broader importance of IFC’s core mission to drive job creation and economic development by supporting expansion of well-governed, sustainable, and thriving private sectors.